A significant and persistent rise in the global burden of adolescent NAFLD and NASH estimated by BMI - Lin, Xiao-Yun; Li, Jing-Mao; Huang, Ling-Yi; Lin, Li-Yan; Hong, Mei-Zhu; Weng, Shangeng; Pan, Jin-Shui (Frontiers in Public Health, 2024)
Currently, there is a lack of global or even country/regional level data on adolescent non-alcoholic fatty liver disease (NAFLD) prevalence. However, an evidenced dose-dependent relationship exists between body mass index (BMI) and the risk of NAFLD. We aim to estimate the global and regional prevalence of adolescent NAFLD and related non-alcoholic steatohepatitis (NASH) based on BMI.Sigmoidal fitting curves were generated between BMI and the risk of NAFLD/NASH using the data extracted from the NHANES database. With global and regional BMI data from the NCD-RisC database, adolescent NAFLD/NASH prevalence was estimated at the international, regional, and country levels from 1975 to 2016. The prevalence of adolescent NAFLD/NASH from 2017 to 2030 was also forecasted.The mean NAFLD prevalence was 15.31%, and 12.68%, while the mean NASH prevalence was 2.50%, and 2.47%, in boys, and girls aged 12-18, respectively. For both boys and girls, NAFLD/NASH prevalence increased with increasing BMI, and age. The global prevalence of adolescent NAFLD/NASH has gradually increased in the period from 1975 to 2016 and will maintain a similar trend between 2017 and 2030. High-income Western Countries had higher adolescent NAFLD/NASH whereas